A positive family history of cancer or lifestyle factors may not explain the high incidence of early-onset colorectal cancer in India. (October 2014) - Raman, Ratheesh; Kotapalli, Viswakalyan; Vamsy, Mohana; Patnaik, Sujit C; Srinivasulu, Mukta; Bashyam, Murali D
SUMMARY : Aim: Colorectal cancer (CRC) patients from developing countries such as India exhibit distinct clinico-pathological characteristics including an early age of onset and predominant tumor localization in the rectum. However, the reason(s) for increased occurrence among the young is not clear.Materials & methods: In the current study, we performed a comparative analysis of several epidemiological features in early and late-onset CRC patients from India including association with familial syndromes, diet and lifestyle habits.Results: Surprisingly, there was no significant association of any epidemiological variable with early-onset CRC.Conclusion: Perhaps low penetrance syndromes and/or other genetic causes may be responsible for an early age of onset among Indian CRC patients.